(untitled) (Raíces: Revista de Ciencias Sociales y Políticas, 2019)
Purpose: The care crisis affecting European countries such as Spain has triggered, in the last 10 years, an increase in female migratory flows from Guatemala and Nicaragua, among others. These women migrate to take care of dependent people while leaving their families in their home countries giving rise to so-called transnational families. The objective of this article is to reflect on the strategies that migrants use to maintain the emotional bond with their loved ones, and then continue with their care efforts. Methodology: Based on a qualitative methodology, during the years 2009 to 2016 we conducted in-depth interviews with Guatemalans and Nicaraguans who have migrated to Spain with the aim of working and who are still in communication with their families in their cities of origin. Results: The analysis of the empirical material reflects firstly that Central American women are migrating to Spain to dedicate themselves to home employment and care, secondly that the physical separation of their families is not an impediment to continue their tasks of careful, thirdly, what importance of the new information and communication technologies for the establishment of a relational proximity across borders. Implications: This article aims to contribute new information to the dynamics of Central American women in Spain, which are characterized by being a relatively new migrant collective and therefore, little studied so far.